2016
DOI: 10.1016/j.electstud.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Turning against the Union? The impact of the crisis on the Eurosceptic vote in the 2014 European Parliament elections

Abstract: Abstract:The 2014 European Parliament elections were held against the backdrop of the worst economic crisis in post-war Europe. The elections saw an unprecedented surge in support for Eurosceptic parties. This raises the question of whether the crisis, and the EU's response to it, can explain the rise of Eurosceptic parties. Our analysis of the 2014 European Election Study demonstrates that the degree to which individuals were adversely affected by the crisis and their discontent with the EU's handling of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(96 citation statements)
references
References 35 publications
(38 reference statements)
1
90
0
1
Order By: Relevance
“…These challenger parties also effectively use populist rhetoric that pits 'ordinary people' against the political establishment. Recent studies have shown that the rise in support for these challenger parties reflect similar divides to those identified in the Brexit campaign with higher levels of support for Eurosceptic parties among the less educated, people adversely affected by the Eurozone crisis, and among those who oppose immigration and multiculturalism (see Hobolt and De Vries 2016b;Hobolt and Tilley 2016). There is a growing divide, both economically and culturally, between those who feel left behind by the forces of globalization and those who feel they have benefitted from it.…”
Section: Is Britain An Outlier?mentioning
confidence: 98%
“…These challenger parties also effectively use populist rhetoric that pits 'ordinary people' against the political establishment. Recent studies have shown that the rise in support for these challenger parties reflect similar divides to those identified in the Brexit campaign with higher levels of support for Eurosceptic parties among the less educated, people adversely affected by the Eurozone crisis, and among those who oppose immigration and multiculturalism (see Hobolt and De Vries 2016b;Hobolt and Tilley 2016). There is a growing divide, both economically and culturally, between those who feel left behind by the forces of globalization and those who feel they have benefitted from it.…”
Section: Is Britain An Outlier?mentioning
confidence: 98%
“…Consequently, economic factors play an important role in attitudes toward integration-particularly after the eurozone economic crisis. 5 While not all Europeans have had the same experiences with integration, some faced fierce job competition with the inflow of foreign workers. In short, there were winners and losers in the process of European integration.…”
Section: Argumentmentioning
confidence: 99%
“…The decline in EU support was more related to the Euro crisis, rather than the global economic slowdown, and thus thisrelationship was more pronounced in the Eurozone countries (Braun & Tausendpfund, ). The impacts ofthe crisis have also resulted in an increase in voting for Eurosceptic parties in the elections for the European Parliament in 2014, which were held against the backdrop of the apogee of the crisis (Hobolt & De Vries, ). In the case of Greece for instance, a country that has been the worst hit by the euro‐crisis and austerity measures,the negative impacts of those appear to be the drivers of Eurosceptic vote and a shift towards morenegative image of the EU (Verney, ), even if, despite this “sea change” in thecitizens' perceptions of the EU, the support for the common currency and staying in the EU remained strong (Clements, Nanou, & Verney, ).…”
Section: Introductionmentioning
confidence: 99%